P62/sequestosome-1 knockout delays neurodegeneration induced by Drp1 loss. (July 2018) - Yamada, Tatsuya; Adachi, Yoshihiro; Yanagawa, Toru; Iijima, Miho; Sesaki, Hiromi
Abstract: Purkinje neurons, one of the largest neurons in the brain, are critical for controlling body movements, and the dysfunction and degeneration of these cells cause ataxia. Purkinje neurons require a very efficient energy supply from mitochondria because of their large size and extensive dendritic arbors. We have previously shown that mitochondrial division mediated by dynamin-related protein 1 (Drp1) is critical for the development and survival of Purkinje neurons. Drp1 deficiency has been associated with one of the major types of ataxia: autosomal recessive spastic ataxia of Charlevoix Saguenay. Using post-mitotic Purkinje neuron-specific Drp1 knockout (KO) in mice, we investigated the molecular mechanisms that mediate the progressive degeneration of Drp1-KO Purkinje neurons in vivo. In these Purkinje neurons, p62/sequestosome-1, a multi-functional adaptor protein that balances apoptotic cell death and cell survival, was recruited to large mitochondria resulting from unopposed fusion in the absence of mitochondrial division. To test the role of p62 in Drp1-deficient neurodegeneration, we created mice lacking both Drp1 and p62 and found that the additional loss of p62 significantly extended the survival of Purkinje neurons lacking Drp1. These results provide insights into the neurodegenerative mechanisms of mitochondrial ataxia and a critical foundation for therapeutic interventions for this disease. Highlights: p62 accumulates on mitochondria in Purkinje neurons lacking Drp1. The knockout of p62 slows Purkinje neuron death caused by the lack of Drp1. p62 acts downstream of ROS-induced morphological transformation of mitochondria.